The Effect of Body Posture Correction on Pain of Musculoskeletal Disorders in Nurses of Intensive Care Unit - Nahid Mohammadi; Maryam Yaghoubi; Roya Amini; Leli Tapak (Hamadan University of Medical Sciences, 2018)
Introduction: intensive care unit nurses are at risk of musculoskeletal disorders due to activities such as moving patients and lifting heavy objects during nursing care. The aim of this study was to determine the effect of body posture correction on musculoskeletal disorders in Nurses. Methods: This pre and post-test quasi-experimental study with two groups (case & control) was performed on 101 nurses working in intensive care unit in 2017. The sampling method was multistage sampling. At first, we selected two hospitals from four hospitals and after selecting nurses, they were divided randomly into case and control groups. Both groups completed 25 questions of the Nordic questionnaires before the intervention. Then in the case group, four sessions of 60 minutes were performed weekly .The nurses were also encouraged to perform stretching exercises for the neck, shoulder and upper limbs. Three months later, two groups completed the questionnaire again. Data was analyzed by SPSS24 software using Wilcoxon test, Covariance analysis and regression analysis. Results: The two groups were matched at the beginning of the study and did not have a significant difference (P<0.05). According to Nordic questionnaire, the highest prevalence of pain before training was in the waist (77.3%), back (46.5%) and head neck (45.5%), which was decreased after the intervention to 41%, 17.9% and 20% respectively in the case group (P<0.05). Conclusion: Regarding the effect of educational intervention on musculoskeletal pain disorders, all nurses must be trained for body posture correction at the beginning or during their work.